2022
DOI: 10.1186/s12944-022-01648-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sampson equation for LDL-C in acute coronary syndrome patients: a Chinese population-based cohort study

Abstract: Objective Low-density lipoprotein cholesterol (LDL-C) is an important cardiovascular disease marker that is used to estimate the risk of acute coronary syndrome in patients. The Sampson equation is an accurate LDL-C equation, but its application in Chinese patients is unclear. Methods This study enrolled 12,989 consecutive Chinese patients with the acute coronary syndrome (ACS), LDL-C levels were determined by direct standard method and two indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…In 2018, the Multi-society Cholesterol Guidelines [ 4 ] specifically recommended that the M-LDL-C equation [ 15 , 20 ] be used for low LDL-C samples but did not comment on the use of F-LDL-C equation for other types of samples. Results from this study and now many other studies [ 10 , 27 , 28 , 29 ] have clearly shown that the F-LDL-C equation does not offer any advantages over more recently developed equations for calculating LDL-C. It may take a more explicit recommendation from future US guidelines discouraging the use of the F-LDL-C equation, at least for samples with more than modest elevations in TG, before more clinical laboratories will switch their LDL-C calculation method.…”
Section: Discussionsupporting
confidence: 78%
“…In 2018, the Multi-society Cholesterol Guidelines [ 4 ] specifically recommended that the M-LDL-C equation [ 15 , 20 ] be used for low LDL-C samples but did not comment on the use of F-LDL-C equation for other types of samples. Results from this study and now many other studies [ 10 , 27 , 28 , 29 ] have clearly shown that the F-LDL-C equation does not offer any advantages over more recently developed equations for calculating LDL-C. It may take a more explicit recommendation from future US guidelines discouraging the use of the F-LDL-C equation, at least for samples with more than modest elevations in TG, before more clinical laboratories will switch their LDL-C calculation method.…”
Section: Discussionsupporting
confidence: 78%
“…The new Sampson formula reported by Sampson et al is a better alternative for estimating LDL-C than conventional methods ( 18 ). Quite a few studies proved that Sampson's formula is more accurate than Friedewald's formula, even when TG is above 800 mg/dL ( 45 , 46 ). Given the above reasons, it is reasonable to estimate RC using the Sampson formula.…”
Section: Discussionmentioning
confidence: 99%
“…External validation of Martin’s method has been conducted in multiple national and international datasets ( 8 , 26 28 ), including those who received PCSK9i [Evolocumab ( 29 ) and Alirocumab ( 30 )]. Li et al discovered that the Sampson equation is more accurate for determining LDL-C in Chinese patients with acute coronary syndrome than the Friedewald equation ( 31 ). In 2020, Sampson et al developed a new equation to estimate LDL-C with high reliability ( 14 ).…”
Section: Discussionmentioning
confidence: 99%